2017
DOI: 10.1038/srep46482
|View full text |Cite
|
Sign up to set email alerts
|

Rational development of a protective P. vivax vaccine evaluated with transgenic rodent parasite challenge models

Abstract: Development of a protective and broadly-acting vaccine against the most widely distributed human malaria parasite, Plasmodium vivax, will be a major step towards malaria elimination. However, a P. vivax vaccine has remained elusive by the scarcity of pre-clinical models to test protective efficacy and support further clinical trials. In this study, we report the development of a highly protective CSP-based P. vivax vaccine, a virus-like particle (VLP) known as Rv21, able to provide 100% sterile protection agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(77 citation statements)
references
References 64 publications
2
73
0
2
Order By: Relevance
“…For these reasons, we consider that the partial sterile protection observed in this study is at least equivalent to the previous results. Regarding other formulations that were able to confer a higher level of protection in murine models, such as Rv21 [17], the comparison is even harder: not only is the immunization route different (i.m. vs. s.c.), but transgenic parasites were also constructed using different approaches [17,36] and the challenge systems vary from i.v.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, we consider that the partial sterile protection observed in this study is at least equivalent to the previous results. Regarding other formulations that were able to confer a higher level of protection in murine models, such as Rv21 [17], the comparison is even harder: not only is the immunization route different (i.m. vs. s.c.), but transgenic parasites were also constructed using different approaches [17,36] and the challenge systems vary from i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies directed against the PvCSP central repeats domain can neutralize the sporozoite infectivity, allowing for the acquisition of sterile protection [16]. A VLP formulation containing PvCSP-based antigens (VK210 and VK247) combined with HBsAg showed promising results both alone and in combination with other antigens [17,18]. However, other studies have demonstrated the importance of the three alleles in conferring worldwide protection against P. vivax malaria based on the newly developed CSP-based vaccine [19].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative strategy embraces the use of informatics to predict and assess MHC-II T-cell epitopes using criteria to maximize their in vivo protective potential. The fastgrowing application of VLP-based vaccines against several parasites, including Plasmodium spp [34,35], Leishmania infantum [36], Toxoplasma gondii [37], Trichinella spiralis [38], and Clonorchis sinensis [39] prompted our interest in developing a VLP-based vaccine against trichuriasis.…”
Section: Discussionmentioning
confidence: 99%
“…This synergistic effect was only evident when the two vaccines were mixed and administered into two legs. Another study, testing different vaccine delivery platforms targeting P. vivax CSP using chimeric RMP that expressed P. vivax CSP, demonstrated that superior immunogenicity was generated by virus-like particles (VLP) expressing P. vivax CSP compared to other formulations, including viral-vectored vaccines or protein plus adjuvant [40].…”
Section: Chimeric Rodent Parasites Expressing Human Plasmodium Proteinsmentioning
confidence: 99%